Exploring Otherness in Toni Morrison’s “Beloved”: A Postcolonial Ecocritical Perspective - El Mitry , Abdelghani (International Journal of Language and Literary Studies, 2024)
This article delves into the concept of otherness in Toni Morrison’s novel “Beloved” through a postcolonial ecocritical lens. By examining the interactions between characters and their environment, the article aims to explore how notions of identity, power, and belonging are shaped by historical and environmental contexts. Key themes such as slavery, trauma, memory, and the impact of the past on the present are analyzed through the perspectives of postcolonial theory and ecocriticism. Through this analysis, the article seeks to uncover the complexities of otherness in the novel and its implications for understanding the relationships between humans, nature, and society. Employing close reading technique, this article tries to answer the following questions:1- How does the postcolonial ecocritical approach enhance our understanding of the concept of otherness in “Beloved”? 2- In what ways do historical and environmental factors influence the construction of otherness in the novel? 3- How do characters in “Beloved” navigate issues of identity, power, and belonging in relation to the concept of otherness?